2009
DOI: 10.1002/jsfa.3532
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant and radical‐scavenging activities of Periploca laevigata root bark extracts

Abstract: BACKGROUND: The root powder of Periploca laevigata is used for preparing soft drinks and as an aromatic in Tunisia. The infusion or decoction of its root bark has widespread use in folk medicine. The plant is used to treat digestive disorders and hypertensive effects as well as other health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 76 publications
3
18
0
Order By: Relevance
“…In addition, the plant extracts was significantly higher than that of the standards. The observed reductive potential of the extracts is as a result of the presence of hydrophilic polyphenolic compounds (Mohammed et al, 2008;Omoruyi et al, 2012). The finding is in full agreement with other reports which showed that the reductive potential of plant extracts corresponds with the amount of phenolic constituents present (Amin et al, 2006).…”
Section: Antioxidant Assaysupporting
confidence: 91%
“…In addition, the plant extracts was significantly higher than that of the standards. The observed reductive potential of the extracts is as a result of the presence of hydrophilic polyphenolic compounds (Mohammed et al, 2008;Omoruyi et al, 2012). The finding is in full agreement with other reports which showed that the reductive potential of plant extracts corresponds with the amount of phenolic constituents present (Amin et al, 2006).…”
Section: Antioxidant Assaysupporting
confidence: 91%
“…The reduction capacity of the extract depends on the presence of reductones, which break the free radical chain by donating a hydrogen atom (Mohamed et al, 2009). In the present Study, an increase in reducing power with an increase in the concentration of the extract have been observed which is in agreement with the reports of Kumar et al, (2012) and Kalaivani and Mathew (2010).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings concurred with other studies [23,26] that reported that the reducing power of plant extracts from different solvents was concentration-dependent. The reducing ability of plant extracts to transform Fe 2+ to Fe 3+ could be a result of the presence of hydrophilic polyphenolic compounds such as lycopene [27].…”
Section: Free Radical Scavenging Activitiesmentioning
confidence: 99%